(untitled) - Bultinck, Bert. (Boston, 2005)
"Outlandish as it may seem to the uninitiated, the meaning of English cardinal numbers has been the object of many heated and fascinating debates. Notwithstanding the numerous important objections that have been formulated in the last three decades, the (neo-)Gricean, scalar account is still the standard semantic description of numerals. In this book, Bultinck writes the history of this implicature-driven approach and demonstrates that it suffers from methodological insecurity. He argues that the implicature-based approach (i) postulates highly non-conventional meanings of numerals as their ’literal meaning’, (ii) fails to make a proper distinction between lexical semantics and utterance meaning, and (iii) cannot deal with a large number of counterexamples. Based on the results of an extensive corpus analysis, an alternative account of the meaning of English cardinals and the ways in which their interpretation is influenced by other linguistic elements is presented. As such, this analysis constitutes a prism that offers today’s linguist an iridescent history of one of the most fascinating, if often misconstrued, topics in contemporary meaning research: the conversational implicatures."--BOOK JACKET.
Keywords: English language,English language,Cardinal numbers.,Tiếng Anh; Numerals.,Semantics.,Số học